Water Security, Justice and the Politics Rights in Peru and Bolivia (Alternautas, 2022)
The overall goal of Water Security, Justice and the Politics of Water Rights in Peru and Bolivia is to scrutinize the claim by legislators, policymakers and development institutes that legal recognition of local water rights reduces water conflict and increases water security and equality for peasants and indigenous communities. This is indeed an ambitious goal of the author Miriam Seemann, given the fact that nearly no studies have looked at the actual impacts of water rights formalization policies on the ground so far. Nonetheless, the book touches a subject of major importance in view of the trend towards the adoption of new water legislations in the last decades, resulting in the formalization of water rights and entitlements, not only in Latin-American countries such as Chile, Brazil, Mexico, Peru and Bolivia, but on a global scale (Baillat 2010). Well aware of the shortcomings of mainstream approaches to property rights formalization, like de Soto's (2000) theoretical presupposition that formal property rights are the most important institution for economic growth and development, the book demonstrates that uncritical formalization of local water rights may lead to weakening, instead of strengthening, local water security.